Respons guru SMPN 1 Bantaeng terhadap workshop budidaya tanaman sistem hidroponik - Sitti Rahma Yunus; Muhammad Aqil Rusli; Muhammad Tawil (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Bantaeng SMPN1 is a school located in the heart of Bantaeng. Narrow school land becomes an obstacle in the cultivation of plants in the school area as an important part of the implementation of Adiwiyata school. For this reason, a crop cultivation system that is suitable for narrow land is needed, the hydroponic system. Unfortunately the teachers at the school do not yet have the knowledge and skills regarding the cultivation of hydroponic systems. Based on this reason, through the Community Partnership Program (PKM), a workshop was held to train the teachers of SMPN 1 Bantaeng in the cultivation of hydroponic systems. The objectives of this program are (1) to provide knowledge and to practice the cultivation skills of hydroponic system plants through workshops and (2) to obtain information on participants' responses to the materials and methods for conducting the workshop. The method used in the workshop is the provision of information (lectures), demonstrations, practice, and assistance. The results obtained after conducting the workshop and giving questionnaire responses were (1) participants gained knowledge and skills in the cultivation of hydroponic system plants (2) participants' responses to the workshop materials and methods were in the high category. These results were also supported by participants' statements that the workshop opened their insights on hydroponic system cultivation.